Predictive factors' modeling of entrepreneurial opportunities in international companies - Ali Farahani; Younos Vakil Alroaia; Farideh Haghshenaskashani; Ali Faez (ارزش آفرینی در مدیریت کسب و کار)
Abstract The purpose of this research is to design a model of predictive factors of entrepreneurial opportunities in international companies. The research method is applicable in terms of purpose, and qualitative in terms of its implementation. The statistical population of the research includes 17 managers and experts active in the field of entrepreneurship, and the sampling was done in a purposeful and snowball manner, and the interviews continued until reaching theoretical saturation. The data collection tool is a semi-structured interview. Data-based method was used to collect and analyze data. Data analysis and pattern design were done in three stages of open, central, and selective coding. For data analysis, MAXQDA 18 software was used for coding. In the open coding stage, 305 preliminary codes were identified out of the analysis of the interviews. In the second stage; core coding based on research findings, the concept of entrepreneurial opportunities was chosen as the core phenomenon. Causal conditions were placed in the form of seven categories: unexpected events, changes based on industry and market structure, shortage based on methods, contradictory situation, change based on values and knowledge, new knowledge, and demographic characteristics; and the four main categories were selected include organizational strategies, market related strategies, business strategies, and effective performance management. Intervening factors were identified in two strengthening and weakening categories. Capital, corporate factors, social learning, gathering and studying information, individual characteristics, and social factors were determined as the background factors of entrepreneurial opportunities. Finally, the consequences of predictors of entrepreneurial opportunities were determined in two categories: financial and tangible, and non-financial and intangible. Extended Abstract Introduction According to entrepreneurship researchers, opportunity identification plays a very fundamental role in entrepreneurial activities. Entrepreneurship creates and recreates value for owners and beneficiaries, and opportunity is the heart of this process. Although opportunity recognition is considered the main characteristic of entrepreneurs and entrepreneurial activity does not occur without it, not all people are able to recognize opportunities; thus not all people can achieve entrepreneurial activities (Jaber et al, 2022). Several studies have been conducted regarding the factors affecting opportunity identification to become the basis for increasing the identification of entrepreneurial opportunities. However, due to the importance of identifying opportunities in the entrepreneurial process, there is still a gap in studies in this field (Virasa et al, 2022). Identifying entrepreneurial opportunities is a relatively new issue that is known as an effective and sustainable solution for the economic and social development of countries, and attracts the attention of wider sections of society every day. The importance of identifying entrepreneurial opportunities is due to the fact that finding predictive factors are effective in identifying profitable opportunities that can be implemented in most parts of the world. Our country is also on the path of taking steps towards development and progress, and putting forward a comprehensive research on factors predicting entrepreneurial opportunities in Iran can help accelerate the process of progress. On the other hand, Iran is a country that has a long and fruitful history in the field of entrepreneurial activities, and attention to a new approach in this field leads to the actualization of the potential capabilities in this field (Abdi, 2015). Based on this, the current research is looking for an answer to this question: How is the design of the model of predictive factors of entrepreneurial opportunities in international companies? Theoretical Framework Entrepreneurship Entrepreneurship is a management attitude that gives meaning to concepts such as innovation, flexibility and accountability based on understanding environmental opportunities. Organizational entrepreneurship occurs when an organization relies on the growth and use of new opportunities of internal and external factors of its organization (Davali et al, 2022). Entrepreneurial opportunities An entrepreneurial opportunity includes a set of ideas, beliefs, and actions that make it possible for them to create future products and services in the absence of current markets. Identifying an entrepreneurial opportunity is the understanding of the possibility of creating a new business or specifically improving the existing situation of a business in such a way that leads to a new profitability potential. In other words, identifying an entrepreneurial opportunity is the ability to identify a good idea and turn that idea into a business concept that has value and economic returns (Scott & Scott, 2016). Panahi et al, (2024) investigated the impact of entrepreneurial intention on students' entrepreneurial behavior regarding the moderating role of fear of failure and economic literacy. The results of the research showed that the variables of independence, innovation, and risk-taking of students have a positive and significant effect on entrepreneurial intention. Also, entrepreneurial intention has a positive and significant effect on entrepreneurial behavior. The fear of failure variable has a negative adjustment of the relationship between intention and behavior, and the economic literacy variable has a positive adjustment on this relationship. The research findings show the important role of personality traits on entrepreneurial intention and the importance of moderators introduced to fill the gap between entrepreneurial intention and behavior. Fries & Jilnek (2023) investigated the psychology of entrepreneurship: action and process in a research. This study reviews entrepreneurial psychology research in the last decade; and focuses on two key themes in entrepreneurship research: action, and process. By combining action and process in a model of entrepreneurial psychology, the process model presents the theory of entrepreneurial action, which is used as a guiding framework for investigation. Theories of action are discussed, such as cause/effect, bricolage, theory of planned behavior, and action theory. In addition, they adopt a process perspective to discuss the antecedents of actions in terms of cognition, motivation, and emotions; and how they develop during the entrepreneurial process. The results of the research showed that the action theory process model is a useful starting point for explaining the psychological dynamics of entrepreneurship. Research methodology The research method is applicable in terms of purpose, and qualitative in terms of its implementation. The statistical population of the research includes 17 managers and experts active in the field of entrepreneurship, and the sampling was done in a purposeful and snowball manner, and the interviews continued until reaching theoretical saturation. The data collection tool is a semi-structured interview. Data-based method was used to collect and analyze data. Research findings Data analysis and pattern design were done in three stages of open, central, and selective coding. For data analysis, MAXQDA 18 software was used for coding. In the open coding stage, 305 preliminary codes were identified out of the analysis of the interviews. In the second stage; core coding based on research findings, the concept of entrepreneurial opportunities was chosen as the core phenomenon. Causal conditions were placed in the form of seven categories: unexpected events, changes based on industry and market structure, shortage based on methods, contradictory situation, change based on values and knowledge, new knowledge, and demographic characteristics; and the four main categories were selected include organizational strategies, market related strategies, business strategies, and effective performance management. Intervening factors were identified in two strengthening and weakening categories. Capital, corporate factors, social learning, gathering and studying information, individual characteristics, and social factors were determined as the background factors of entrepreneurial opportunities. Finally, the consequences of predictors of entrepreneurial opportunities were determined in two categories: financial and tangible, and non-financial and intangible. Conclusion The current research was conducted with the aim of designing a model of predictive factors of entrepreneurial opportunities in international companies. The results of this research are in agreement with the results of Panahi et al, (2024), Fries & Jilnek (2023), Abadeh et al, (2022), BurujAli (2022), Jaber et al, (2022), Doanh (2021), Bazkiaei et al, (2020), Hamzeh Ni Tehrani et al, (2022), Ghanizadeh et al, (2020), Zivodar (2019), Ahmadi et al, (2018), and Vaghely & Julien (2015). Hamzeh Ni Tehrani et al, (2022) in their research confirmed the factors of personality characteristics and environmental factors as strengthening factors in discovering entrepreneurial opportunities. Effective strategies on the discovery of entrepreneurial opportunities were also, by identifying sixty-five concepts, placed in the form of six sub-categories and four main categories of organizational strategies, market-related strategies, business strategies, and effective performance management. According to the results of the research, the following suggestions are presented: - continuous monitoring of changes and trends in society; these changes, which are influenced by social and economic factors and government policies, create new challenges and opportunities for companies that can make the best use of these opportunities with careful planning; - Creating an open communication channel in the company environment; If there is no open communication in the workplace, people's creativity will be damaged. To bring innovation to the workplace, employees must be informed that the door is always open for discussion